2020
DOI: 10.2147/ijgm.s257340
|View full text |Cite
|
Sign up to set email alerts
|

<p>Patient-Reported Outcomes and Economic Burden of Adults with Sickle Cell Disease in the United States: A Systematic Review</p>

Abstract: Purpose: To systematically estimate the patient-reported outcomes (PROs) and economic burden of sickle cell disease (SCD) among adults in the United States (US). Patients and Methods: Two systematic literature reviews (SLRs), one each for the PROs and economic topics, were performed using MEDLINE and Embase to identify observational studies of adults with SCD. Included studies were published between 2007 and 2018 and evaluated health-related quality of life (HRQL), function, healthcare resource utilization (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 41 publications
0
31
1
Order By: Relevance
“…These findings are conflict with the results conducted by Tabuk and Gana's study that showed the rate of depression is higher in females [11,21]. Similarly, the results reported by the Southern Region of Saudi Arabia also show the rate of depression and anxiety is higher in females [19]. However, these results failed to indicate any statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings are conflict with the results conducted by Tabuk and Gana's study that showed the rate of depression is higher in females [11,21]. Similarly, the results reported by the Southern Region of Saudi Arabia also show the rate of depression and anxiety is higher in females [19]. However, these results failed to indicate any statistical significance in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…This study aimed to determine the prevalence and identify the relationship of sociodemographics with depression and anxiety of SCD patients at King Abdulaziz University Hospital, Jeddah, Saudi Arabia. Other researches found that depressed patients will have significantly higher health care utilization and inpatient costs than nondepressed patients [17][18][19]. So determining the risk factors that increase a psychological disorder in SCD patients will be a chance to decrease the cost and provide much better medical care to these patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 A recent systematic review found depression and anxiety occurrence to be 21-33% and 7-36%, respectively, in adults with SCD. 5 Higher pain is also strongly associated with decreased work and school activity, social activity, and household chores. 6 Thus, new interventions are needed to improve the overall quality of life of patients with SCD in addition to pain outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Additionally, the disease burden to the patient imparts a shortened lifespan and the loss of potential income, in addition to a substantial detriment to the quality of life. 7,8 Despite the substantial personal and societal burden of SCD, compared with other genetic disorders SCD has received relatively little attention and minimal resources since it was first described in 1910. Investments in discoveries and clinical care infrastructure have been limited and have not kept pace with other equally devastating but less common inherited conditions.…”
Section: The Unmet Needs Of Individuals With Scdmentioning
confidence: 99%